Exploiting Knowledge on Leishmania Drug Resistance to Support the Quest for New Drugs. Issue 3 (March 2017) - Hefnawy, Aya; Berg, Maya; Dujardin, Jean-Claude; De Muylder, Géraldine
Abstract : New drugs are needed to control leishmaniasis and efforts are currently on-going to counter the neglect of this disease. We discuss here the utility and the impact of associating drug resistance (DR) studies to drug discovery pipelines. We use as paradigm currently used drugs, antimonials and miltefosine, and complement our reflection by interviewing three experts in the field. We suggest DR studies to be involved at two different stages of drug development: (i) the efficiency of novel compounds should be confirmed on sets of strains including recent clinical isolates with DR; (ii) experimental DR should be generated to promising compounds at an early stage of their development, to further optimize them and monitor clinical trials. Trends: Robust chemotherapy is a major element among strategies of disease control. Thus, treatment failure and drug resistance (DR) are one of the major risk factors for (re-) emergence and spreading of leishmaniasis worldwide. It is essential to protect the few existing drugs as well as the new coming ones against DR. Antimonials (SSG) have been abandoned in the Indian subcontinent (ISC) after decades of use. SSG-DR studies show that experimental resistance is predictive of what has been observed in clinical situations. The knowledge on SSG-DR could have been used to counter resistance, by guiding the choice of combination therapy or the most adequate liposomal formulation. Miltefosine (MIL) has replaced SSG in the ISC. After a decade of use, efficacy dropped significantly, but so far, this was not associated with MIL-DR. In parallel, mechanisms of experimental MIL-DR have been unraveled. It may be a question of time before MIL-DR emerges and spreads in the ISC. If/when this occurs, it is likely that mechanisms will be the same as in experimental studies. MIL-DR can be countered by combination therapy or by formulations that overcome reduced uptake of MIL. DR studies are not yet incorporated in drug discovery pipelines for leishmaniasis. We argue that these could be implemented in one of two ways: (i) drug-resistant clinical isolates should be included in high-throughput drug-screening assays to account for parasite diversity; (ii) in vitro selection of resistant parasites should be performed on new lead compounds to uncover their target and optimize their design.